Unusual occurrence of brain hydatid disease in a patient with previous surgical intervention for hemorrhagic venous infarct - Reddy, V Umamaheshwar; Reddy, Sai Keerthana Dhani; S, Sankeerthy; Agrawal, Amit (Indian Journal of Case Reports, 2018)
Hydatid disease is an endemic parasitic disease and can occur anywhere in the body and has a variable presentation. On imaging, thelesions have varied appearance ranging from cystic to solid appearing lesions, solitary to multiples. We present a case of 35-year-oldfemale who underwent decompression craniectomy for right temporoparietal hemorrhagic venous infarct and now presented withacute onset of right-sided weakness. Magnetic resonance imaging was suggestive of cerebral hydatid disease. The presented caseemphasizes that hydatid cyst should be considered as a possibility whenever a cystic lesion is encountered during imaging.